Thought piece: to what extent could the reflective approach to teaching practicum debriefing strategy be incorporated in lesson study?. Issue 1 (2nd January 2022) - Minott, Mark
ABSTRACT: This thought piece draws the readers' attention to the pervasive nature of reflection, reflective teaching and learning and the use of questions. Specifically discussed; are the theoretical framework that guides the piece, reflective teaching, the reflective approach to teaching practicum debriefing (RATPD) and lesson study. Provided is an example that incorporates the RATPD primarily in the post-lesson discussions/colloquia while being faithful to the collaborative nature of lesson study. Achieving these answers the question: 'To what extent could the reflective approach to teaching practicum debriefing strategy be incorporated in lesson study?' The piece ends with a question that challenges readers to conclude and perhaps engage in further reflection on the discussed topic.